Discursive displacement, strategic peopling: constructions of self-identity and nation in Ian Douglas Smith's Bitter harvest: the great betrayal and the dreadful aftermath and Peter Godwin's Mukiwa — a white boy in Africa. - Javangwe, Tasiyana D. (Unisa Press, 2016)
This article explores how the life narratives of Ian Douglas Smith, Bitter harvest the great betrayal and the dreadful aftermath (1997), and Peter Godwin, Mukiwa — a white boy in Africa (1996), construct identities of self and the Rhodesian nation through a narrative discourse that seeks to evacuate the Rhodesian cultural space of the perceived others. The article also seeks to argue that these narratives strive to 'people' the evacuated spaces not only physically, but culturally with notions, ideologies and social values of the self and the dominant group to which they belong. In the process, the two narratives are ironically depicted as self-damaging because they promote the exclusion instead of the inclusion of the majority of African people in Rhodesia (now Zimbabwe) in the process of defining the self and the Rhodesian nation.